Rancang Bangun Sistem Informasi Perpustakaan Berbasis Web di SMK Ma’arif Terpadu Cicalengka - Mukti Alimin; Topan Trianto (Jurnal Dimamu, 2022)
Ma'arif Terpadu Cicalengka Vocational School which is located at Jalan Raden Dewi Sartika, Cicalengka Kulon, Kec. Cicalengka, Bandung Regency. Having 1 Admin and 1 Librarian, The purpose to create a design of the library information system is shown as a system created to solve problems in parts that are at risk of losing data such as books and their stock, minimizing loss of recording of borrowing and returning transactions, as well as making reports that take time to process. The purpose of this research is to overcome the problems described above, namely by creating a system that can be used in the Ma'arif Terpadu Cicalengka Vocational High School Library area. Therefore, a Web-based Library Information System Design was made at SMK Ma'arif Terpadu Cicalengka. This thesis is made with a collection of methods that can be used to collect data and information that can be made as a description of the system that is being made. The method used in the development of this system is the RUP (Rational Unified Process) model with OOAD (Object Oriented Analysis and Design) with the development tool UML (Unified Modeling Language). Meanwhile, the diagrams used are: Use Case Diagrams, Sequence Diagrams, Activity Diagrams and Class Diagrams. In addition, the design objectives of this system include recording books and their stock, minimizing loss of recording of borrowing and returning transactions, as well as facilitating the manufacture of reports quickly and accurately.